Follicular Thyroid Neoplasms: Comparison of Clinicopathologic and Molecular Features of Atypical Adenomas and Follicular Thyroid Carcinomas. (July 2020) - Cracolici, Vincent; Ritterhouse, Lauren L.; Segal, Jeremy P.; Puranik, Rutika; Wanjari, Pankhuri; Kadri, Sabah; Parilla, Megan; Cipriani, Nicole A.
Abstract : In follicular thyroid neoplasms without invasion, a diagnosis of atypical adenoma (AA) (follicular tumor of uncertain malignant potential) may be rendered if atypical features (indefinite capsular/vascular invasion, necrosis, solid growth, increased mitoses) are present. This study compares clinical, histologic, and molecular features of patients with AAs (n=31), nonmetastatic follicular thyroid carcinoma (nmFTC) (n=18), and metastatic follicular thyroid carcinoma (mFTC) (n=38). Patients with mFTC were older. Mitotic activity in areas of solid growth was greatest in mFTC ( P =0.05). Oncocytic tumors tended to show solid growth ( P =0.04). The presence or frequency of capsular and/or vascular invasion was not different between nmFTC and mFTC. TERT promoter mutations were higher in patients with mFTC (50%) than nmFTC (25%) and AA (10%) ( P =0.02). TERT promoter mutation was associated with necrosis ( P =0.01) and solid growth plus increased mitoses ( P =0.03). Necrosis and TERT promoter mutations were identified in all groups, most frequently in mFTC. The combination of solid growth with increased mitoses, necrosis, and TERT promoter mutation was only seen in follicular carcinomas. Poorly differentiated features, vascular invasion, and TERT promoter mutation correlated with metastasis in FTC. Given the low frequency of necrosis and TERT promoter mutation in AAs, close clinical follow-up is recommended in patients with these findings, especially if additional atypical features (such as solid growth plus mitoses) are present.